Seroprevalence and serotype distribution of foot and mouth disease virus and associated risk factors in cattle across various export livestock sourcing districts of Bale Zone, Ethiopia - Gizaw, D.; Negessu, D.; Fentie, A.; Muluneh, A.; Asgedom, H.; Guyassa, C.; Ashenafi, H.; Temesgen, Wudu; Legesse, M.; Kassa, T. (Springer, 2024)
Background: Foot and mouth disease (FMD) is a contagious and economically important viral disease affecting cloven-hoofed animals. A cross-sectional study was conducted from January to March 2022 in selected districts of Bale zone, Ethiopia to determine the seroprevalence and serotypes of FMD virus circulating in cattle. Blood samples were collected from cattle and tested for antibodies against non-structural proteins (NSP) of FMD virus using a 3ABC enzyme-linked immunosorbent assay (ELISA). Positive samples were further tested for serotype-specific antibodies using solid phase competitive ELISA (SPCE). Descriptive statistics, both univariable and multivariable logistic regression were used to analyse FMD serostatus and associated risk factors.